STRATEGI BADAN USAHA MILIK DESA (BUMDes) USAHA JAYA DESA BINA MAJU KECAMATAN RANGSANG BARAT KABUPATEN KEPULAUAN MERANTI TAHUN 2022 - Nasoha, Fazli; ,, Adlin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2025)
This study examines the Strategy of Village-Owned Enterprises (BUMDes) Usaha Jaya, Rangsang Barat District, Meranti Islands Regency in 2022. Based on Government Regulation Number 11 of 2021 concerning the Establishment, Management, and Development of BUMDes at the Village Level. This study uses the strategy theory of Anatan and Ellitan which includes three aspects: Technology, Innovation, and Operations. The research approach used is qualitative with data collection techniques in the form of interviews and observations. The results of the study indicate that BUMDes Usaha Jaya Desa Bina Maju has implemented technology, innovation, and operational strategies for However, the Operational strategy still experiences obstacles in the marketing aspect of BUMDes product promotion funds, especially in the use of social media. This study emphasizes the importance of implementing strategies for good BUMDes management by paying attention to supporting factors so that the implementation of programs run by BUMDes will bring benefits that are directly felt by the community. Keywords: strategy, BUMDes, Technology, Innovation, Operations